Smooth time-invariant control for leaderless consensus of networked nonholonomic systems. (26th December 2017) - Xie, Wenjing; Ma, Baoli
This article studies the leaderless consensus control problem of multiple nonholonomic chained systems. Two smooth time-invariant static distributed controllers are derived based on Lyapunov method, graph theory, and LaSalle invariance principle. Both of the proposed controllers guarantee that the states of the multiple nonholonomic systems globally asymptotically converge to a common vector, provided that the interconnection topology is undirected and connected. In particular, the second control scheme can reduce the size of the control inputs via saturated control and is more applicable in real engineering. Several numerical simulations are implemented for kinematic models of four nonholonomic unicycle mobile robots, demonstrating the effectiveness of the proposed control schemes.